2020
DOI: 10.1136/ijgc-2019-001161
|View full text |Cite
|
Sign up to set email alerts
|

Total retroperitoneal en bloc resection of multivisceral-peritoneal packet (TROMP operation): a novel surgical technique for advanced ovarian cancer

Abstract: BackgroundA Total Retroperitoneal en bloc resection Of Multivisceral-Peritoneal packet (TROMP operation) is a no-touch isolation technique in a retroperitoneal space to resect the parietal peritoneum and the affected organs in advanced ovarian cancer. The study prescribed and analysed the results of this novel technique for primary cytoreductive surgery.MethodsThe study included 208 patients operated between January 2015 and December 2017 in Charité, Berlin. The TROMP operation was performed in 58 patients, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
3
6
1
Order By: Relevance
“…The sub-study LION-PAW study has confirmed that lymphadenectomy (unsparing technique) is associated with a higher incidence of post-operative complications, including a significant change of the orgasm score from baseline to 12 months in sexually active patients. This result falls in tandem with the still unpublished findings by the authors on sexual function assessment of advanced ovarian cancer patients [36], who were operated by conventional surgical technique compared with the patients operated with total retroperitoneal en bloc resection of multivisceral-peritoneal packet (TROMP) technique [37] and abovementioned nerve-sparing lymph node dissection. The data have shown a worsened score of discomfort during sexual intercourse and a reduced orgasm score with conventional surgical technique as compared to nerve-sparing lymph node dissection.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The sub-study LION-PAW study has confirmed that lymphadenectomy (unsparing technique) is associated with a higher incidence of post-operative complications, including a significant change of the orgasm score from baseline to 12 months in sexually active patients. This result falls in tandem with the still unpublished findings by the authors on sexual function assessment of advanced ovarian cancer patients [36], who were operated by conventional surgical technique compared with the patients operated with total retroperitoneal en bloc resection of multivisceral-peritoneal packet (TROMP) technique [37] and abovementioned nerve-sparing lymph node dissection. The data have shown a worsened score of discomfort during sexual intercourse and a reduced orgasm score with conventional surgical technique as compared to nerve-sparing lymph node dissection.…”
Section: Discussionsupporting
confidence: 70%
“…Rigorous dissection protocol was in place to interpret the retroperitoneal para-aortic nervous connections to and from the contiguous anatomical structures, with specific reference to lymph node dissection in gynae-oncology. The new anatomical know-how from this cadaver study was utilized to enhance and develop a superior technique for para-aortic lymph node dissection and was efficaciously employed in locally advanced cervical cancer (a cohort of 15) [9] and in advanced ovarian cancer as a part of total retroperitoneal en bloc resection of multivisceral-peritoneal packet (TROMP operation) for advanced ovarian cancer (a cohort of 48) [37,38] and the evidence appositely reported in multiple journals. Approval from the Charité Local Ethics Committee was provided for the clinical parts of this study (EA1/174/14 for cervical cancer patients and EK207/2003 Amendment 15/2012 for ovarian cancer patients) as per the recommendations of the Ethics Commission of the parent institution.…”
Section: Methodsmentioning
confidence: 99%
“…4 This has also been well described in the LION-PAW (lymphadenectomy in ovarian neoplasm-pleasure ability of women) study 5 evaluating prospectively and substantially the role of systematic lymph node dissection (unsparing technique) in advanced ovarian cancer with reference to sexual The authors confirmed that lymphadenectomy (unsparing technique) is associated with a significant change in the orgasm score from baseline to 1 year in sexually active patients. These results are in line with previous results of the total retroperitoneal en bloc resection of multivisceral-peritoneal packet (TROMP) operation study, 6 which included our technique for nerve sparing systematic lymph node dissection. The results confirmed a worse score for discomfort during sexual intercourse and a reduced orgasm score with the conventional surgical technique compared with nerve sparing lymph node dissection.…”
supporting
confidence: 89%
“…Complete peritonectomy was associated with high morbidity (about 40%) and significant mortality (around 4%), especially when combined with visceral resection, and even in experienced hands. In a German study, the rate of postoperative complications for the same surgical technique was 54.5%, higher than the rate in our study [28]. In our study, around 28% of patients had per-operative complications like haemorrhage, bladder injury, diaphragmatic resection and bowel injury and 74% of patients being blood transfused.…”
Section: Discussioncontrasting
confidence: 65%